ANALISIS HARGA SAHAM PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Amillia Astuti (2021)
This research is a quantitative study that aims to determine and analyze the effect of liquidity, profitability, and solvability on stock prices in mining sector companies listed on the Indonesia Stock Exchange in 2016-2019. This study used 24 companies as samples with purposive sampling method. The analytical thechnique used in this research is Panel Data Regression Analysis with the help of the E-Views 10. The results of this study indicate that (1) Liquidity (Current Ratio) has a negative effect on mining stock prices, (2) Profitability (Return On Equity) effect on mining stock prices, (3) Solvability (Debt to Equity Ratio) not effect on mining stock prices